Analysis of the Use of E-Purchasing with Local Catalogs on the Performance of the Central Maluku Regency Government - Ismail; Erly Leiwakabessy; Maryam Sangadji; Fahrudin Ramly (PT Mattawang Mediatama Solution, 2024)
E-purchasing is a method of procurement of goods and services whose process resembles the online shopping system that is rife today such as lazada.com, bukalapak.com, elevenia.com, and others. E-purchasing complements the method of procurement of government goods and services which previously consisted of general auction/selection, limited auction/selection, simple auction, direct appointment, direct procurement, contest and contest. This study aims to determine the effect of efficiency, effectiveness and transparency on the performance of procurement of goods through local catalogs. The population of this study are Procurement Officials, Commitment Making Officials in the Central Maluku Kabuapten Government, and local catalog users in Central Maluku Regency, as well as Goods/Services Providers involved in local catalogs. The sample was determined by purposive sampling technique, as many as 110 respondents. The analysis method used is the Structural Equation Model (SEM). The research variables are 4 latent variables consisting of 3 independent variables each efficiency, effectiveness and transparency and 1 (one) dependent variable namely performance. The results showed that efficiency, effectiveness and transparency had a positive and significant effect on the performance of procurement of goods through local catalogs.